Bacteriophage cocktail for the prevention of biofilm formation by Pseudomonas aeruginosa on catheters in an in vitro model system - Fu, Weiling; Forster, Terri; Mayer, Oren; Curtin, John J; Lehman, Susan M; Donlan, Rodney M (Antimicrobial agents and chemotherapy, 2010)
Microorganisms develop biofilms on indwelling medical devices and are associated with device-related infections, resulting in substantial morbidity and mortality. This study investigated the effect of pretreating hydrogel-coated catheters with Pseudomonas aeruginosa bacteriophages on biofilm formation by P. aeruginosa in an in vitro model. Hydrogel-coated catheters were exposed to a 10 log(10) PFU ml(-1) lysate of P. aeruginosa phage M4 for 2 h at 37 degrees C prior to bacterial inoculation. The mean viable biofilm count on untreated catheters was 6.87 log(10) CFU cm(-2) after 24 h. The pretreatment of catheters with phage reduced this value to 4.03 log(10) CFU cm(-2) (P < 0.001). Phage treatment immediately following bacterial inoculation also reduced biofilm viable counts (4.37 log(10) CFU cm(-2) reduction; P < 0.001). The regrowth of biofilms on phage-treated catheters occurred between 24 and 48 h, but supplemental treatment with phage at 24 h significantly reduced biofilm regrowth (P < 0.001). Biofilm isolates resistant to phage M4 were recovered from catheters pretreated with phage. The phage susceptibility profiles of these isolates were used to guide the development of a five-phage cocktail from a larger library of P. aeruginosa phages. The pretreatment of catheters with this cocktail reduced the 48-h mean biofilm cell density by 99.9% (from 7.13 to 4.13 log(10) CFU cm(-2); P < 0.001), but fewer biofilm isolates were resistant to these phages. These results suggest the potential of applying phages, especially phage cocktails, to the surfaces of indwelling medical devices for mitigating biofilm formation by clinically relevant bacteria.